Excitation of magnetoplasma oscillations in semiconductor structures by fluxes of charged particles - Serkov, Aleksandr; Breslavets, Vitaliy; Yakovenko, Igor; Fomenko, Andrii (Національний технічний університет "Харківський політехнічний інститут", 2021)
The subject of the papers is the processes of analysis and physical model of excitation (amplification) of magnetoplasma oscillations (helicons) by fluxes of charged particles (electrons) in the presence of a constant magnetic field. This model is based on the Cherenkov mechanism for converting kinetic energy of particles into the energy of natural electromagnetic oscillations of solid-state (semiconductor) structures under resonance conditions when the particle velocities coincide with phase velocities of oscillations. The aim here is to justify the formulation of theoretical studies basing on the proposed physical model of generation (amplification) of electromagnetic oscillations (emergence of oscillation instabilities, i.e., exponential growth of their amplitude). We define parameters intervals for the external magnetic field, particle fluxes and types of semiconductor structures which this physical model is applied to. We perform theoretical study of the influence charged particle fluxes have on waveguide characteristics of semiconductor structures. The study justifies the possibility of generation and amplification of magnetoplasma oscillations in the submillimeter range. Our objectives are theoretical studies of the interaction of moving charges with electromagnetic oscillations of a semiconductor structure under conditions of Cherenkov radiation. The methods used are the method of successive approximations for solving the dispersion equations for a system of charged particle flux - semiconductor structure within the framework of hydrodynamic approach. The following results are obtained: Theoretical studies of the functioning of semiconductor components of electrical radio equipment in the presence of charged particle fluxes have been carried out. It is shown that the effect of the particle flux is characterized by the emergence of oscillation instabilities in the semiconductor structure. We have determined one of the mechanisms for the excitation of magnetoplasma oscillations based on the interaction of moving charges with the intrinsic fields of the structures that constitute a semiconductor unit. Such equipment failures occur under conditions of Cherenkov radiation. We have shown that this interaction leads to appearance of a mode of oscillation generation. The results of a comparative analysis of the data obtained in this work make it possible to use the proposed physical model to determine the criteria for the occurrence and development of instabilities of magnetoplasma oscillations. Conclusions. The results obtained in this work can be used in the development of active microwave range devices (amplifiers, generators and transducers of electromagnetic oscillations of the millimeter and submillimeter bands). The comparative analysis of quantitative estimates of the growth rates of oscillation instabilities, depending on the spatial configuration of the acting field (when induced current is parallel to the structure boundary), carried out in this work, provides a solution to the problem of optimizing the operating characteristics of active microwave devices.

Предмет дослідження – процеси аналізу та фізичної моделі збудження (посилення) магнітоплазменних колес (геліконов) потоків заряджених частин (електронів) при наявності постійного магнітного поля. Данна модель базується на черенківському механізмі перетворення кінетичної енергії частинок на енергію власних електромагнітних колекторів твердотільних (напівпровідникових) структур в умовах резонансу, коли швидкість частки та фазові швидкості коливань співпадають. Мета статті – обґрунтування постановки теоретичних досліджень на базі запропонованої фізичної моделі генерації (посилення) електромагнітних коливань (появи нестійкостей коливань, тобто експоненціального поста їх амплітуди). Визначено області параметрів зовнішнього магнітного поля, потоків частинок і типів напівпровідникових структур, при яких реалізується дана фізична модель. Проведено теоретичні дослідження впливу потоків зарядженихчастинок на хвильове характеристики напівпровідникових структур. Вони показали можливість генерації та посилення магнітоплазмових коливань субміліметрового діапазону. Завдання: теоретичні дослідження взаємодії рухомих зарядів з електромагнітними коливаннями напівпровідникової структури в умовах черенковского випромінювання. Методи досліджень: метод послідовних наближень рішення дисперсійних рівнянь системи потік заряджених частинок - напівпровідникова структура в рамках гідродинамічного підходу. Результати досліджень. Проведено теоретичні дослідження функціонування напівпровідникових комплектуючих електрорадіовиробів при наявності потоків заряджених частинок. Показано, що вплив потоку частинок характеризується виникненням нестійкостей коливань напівпровідникової структури. Визначено один з механізмів порушення магнітоплазмових коливань, заснований на взаємодії рухомих зарядів, з власними полями структур, комплектуючих напівпровідниковий виріб. Подібні відмови реалізуються в умовах черенковського випромінювання. Показано, що дана взаємодія проводить до появи режиму генерації коливань. Результати порівняльного аналізу, отриманих в даній роботі розрахункових даних, дозволяють використовувати запропоновану фізичну модель для визначення критеріїв виникнення і розвитку нестійкостей магнітоплазмових коливань. Висновки. Результати, отримані в роботі, можуть бути використані при розробці активних приладів НВЧ-діапазону (підсилювачів, генераторів і перетворювачів електромагнітних коливань міліметрового та субміліметрового діапазонів). Проведений в роботі порівняльний аналіз кількісних оцінок інкрементів нестікостей коливань в залежності від просторової конфігурації впливає поля (наведений струм паралельний кордоні структури) дозволяє вирішувати задачі оптимізації робочих характеристик активних приладів НВЧ-діапазону.
Збудження магнітоплазмових коливань у напівпровідникових структурах потоками заряджених часток
Keywords: charged particle flux; electromagnetic radiation; потік заряджених частинок; електромагнітне випромінювання